The answer is C. y= 3/2 x. You can check by multiplying 3/2 by 3, if you get 7, it is correct
I was stuck on the same thing in my class test. I ended up failing but if I get the answers to it I’ll totally send them to you!!!
Graph D is the answer to this question
Answer:
y = -x² + 6x - 1
General Formulas and Concepts:
<u>Algebra I</u>
- Standard Form: ax² + bx + c = 0
- Expanding by FOIL (First Inside Outside Last)
- Combining like terms
Step-by-step explanation:
<u>Step 1: Define equation</u>
y = -(x - 3)² + 8
<u>Step 2: Rewrite</u>
- Expand [FOIL]: y = -(x² - 6x + 9) + 8
- Distribute -1: y = -x² + 6x - 9 + 8
- Combine like terms: y = -x² + 6x - 1